Multiobjectives bihistogram equalization for image contrast enhancement. Issue 2 (22nd January 2014) - Hum, Yan Chai; Lai, Khin Wee; Mohamad Salim, Maheza Irna
<x xml:space="preserve">Abstract</x> The global histogram equalization (HE) has been the most frequently adopted image contrast enhancement technique. A brightness and detail‐preserving HE method with good contrast enhancement effect has been a goal of much recent research in HE. Nevertheless, producing a well‐balanced HE is deemed to be a daunting task. In this article, we propose a novel framework of HE with the aim of taking three desirable properties into account: brightness preservation, detail preservation, and contrast enhancement. We termed the proposed method as multipurpose beta optimized bi‐HE (MBOBHE). MBOBHE consists of performing the histogram optimization separately in both subhistograms after the segmentation of histogram using an optimized separating point based on the three performance criteria using a weighted‐sum aggregated objective function (AOF). Both quantitative and qualitative results indicate that MBOBHE outperforms other existing bi‐HE methods, in terms of comprehensive performance of HE that is capable of providing a holistic view. © 2014 Wiley Periodicals, Inc. Complexity 20: 22–36, 2014